A Dynamic Composite Web Services Selection Method With QoS-Aware Based on AND/OR Graph - Hong Yu (International Journal of Computational Intelligence Systems, 2014)
Service selection problem refers to the selection of appropriate Web services from a large number of candidates in order to create complex composite services that can satisfy users’ quality-of-service (QoS) requirements. However, the existing services selection methods seldom consider the parallel relations between services as well as the dynamic changing of QoS. To combat these defects, a QoS-aware composite services selection model is presented based on an AND/OR graph model in this paper. The weight of edges is defined by considering QoS attributes, and one shorter path in the model is corresponding to the better service composition that satisfies the service request. Besides, the model is not only capable of dealing with sequence relations and fork relations between services, but also capable of dealing with parallel relations between services. And then a heuristic services selection algorithm is developed based on the framework of the ant colony optimization (ACO) to guide finding the path, and which is able to deal with three cases of the dynamic changing of QoS discussed in this paper. The results of comparison experiments show that the proposed method is effective and efficient.